Design of localized surface plasmon resonance-based refractive index sensor using optical fiber - Yadav, Mukti; Kaler, R.S. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
The paper proposes a design of a localized surface plasmon resonance-based refractive index sensor for the detection of a chemical compound availing unclad geometry of the optical fiber. The geometry is explored to analyze the sensing behavior and coupling phenomenon at the metal-dielectric interface. The finite element method (FEM) is applied numerically to evaluate the analytical change in the reflectance spectra of the fiber model by inoculating potassium nitrate compound. The resonance shift and reflectance of the surface plasmon resonance (SPR) signal obtained after the optimization of structural parameters enhance the sensing performance of the prototype. The sensor exhibits a maximum sensitivity of 80.2919 rad/RIU for a 1.56 high refractive index analyte and minimum sensitivity of 2.3446 rad/RIU for a 1.33 low refractive index analyte. The proposed sensor is modelled in such a way that it can be employed in various sensing applications for a wide range of refractive indices.
Optica Applicata, Vol. 54, 2024, nr 1, s. 85-96
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; localized surface plasmon resonance (LSPR); multi-mode optical fiber; refractive index sensor; sensitivity; COMSOL Multiphysics